RISKS ANALYSIS IN CATERING INDUSTRY - *Tolga Ankaraligil (Rojan GÜMÜŞ, 2019)
In recent years, the occupational health and safety has become one of the important elements of working life. The importance of contributing to the protection of employee health by preventing occupational accidents and occupational diseases is increasing demand nowadays. The rapid growth of the catering sector with increasing employment and competition turn into a growing problem: increase in occupational accidents. In this research carried out with the necessity of taking precautions for the solution of this problem; A risk analysis was conducted in a catering company in Uşak to identify hazards and risks in the company. The hazards and risks are evaluated and precautionary actions were determined according to the current situation. At the same time, it is thought to be beneficial in terms of creating awareness for all companies in the sector by contributing to the protection of employee health by reducing occupational accidents and diseases. Risk analyses were done by L type matrix (5x5 matrix table). In this study, a total of 131 hazards and risks were identified. The identified hazards and risks are grouped according to their risk level (Unacceptable risk: 5; Significant risk:61; Medium risk:59). It is considered that adopting proactive approaches within the scope of occupational safety practices will accelerate the spread of the safety network and occupational safety culture to all employees